Development of a low-cost microclimate monitoring system through IoT, using long-range technology (LoRa) - Camparim, R.; Petenuci, M. E.; Súarez, Y. R. (International Journal of Advanced Engineering Research and Science, 2022)
The Internet of Things (IoT) can be a means of inserting the environment into our daily lives. IoT allows remote monitoring of any area or process, providing greater reliability. Therefore, this work aimed to develop a low-cost microclimate monitoring system through IoT, using long-range (LoRa) technology with radiofrequency communication between the receiver and the transmitter systems. Two WiFi LoRa 32 V2 modules were used to develop data acquisition systems with independent information storage. For microclimate monitoring, temperature sensors, relative air humidity, illuminance, anemometer and a MicroSD card module were used, connected to the data acquisition transmitter system (DAQ_T). This system was packaged into polyvinyl chloride (PVC) tubes for outdoor protection. The modules were programmed through the Arduino IDE (Integrated Development Environment) platform, which permits the development of a web service for real-time data visualization and, as support for monitoring and data storage by the ThingView App. All sensors were tested and compared with reference equipment to ensure its effectiveness and efficiency. After numerous tests, the developed system presented satisfactory results and reached 3.5 km of intermittent communication between receiver and transmitter of the develop system. Consequently, this system could be considered a low-cost option to be applied in microclimate monitoring or environmental monitoring, including places without internet network.